Photochemically Driven Polymeric Network Formation: Synthesis and Applications. Issue 15 (11th January 2017) - Blasco, Eva; Wegener, Martin; Barner‐Kowollik, Christopher
Abstract : Polymeric networks have been intensely investigated and a large number of applications have been found in areas ranging from biomedicine to materials science. Network fabrication via light‐induced reactions is a particularly powerful tool, since light provides ready access to temporal and spatial control, opening an array of synthetic access routes for structuring the network geometry as well as functionality. Herein, the most recent light‐induced modular reactions and their use in the formation of precision polymeric networks are collated. The synthetic strategies including photoinduced thiol‐based reactions, Diels–Alder systems, and photogenerated reactive dipoles, as well as photodimerizations, are discussed in detail. Importantly, applications of the fabricated networks via the aforementioned reactions are highlighted with selected examples. Concomitantly, we provide future directions for the field, emphasizing the most critically required advances. Abstract : Photoinduced polymeric network formation is one of the most employed processes for network fabrication, since light provides ready access to temporal and spatial control. Recent light‐induced modular reactions, such as photoinduced thiol‐based reactions, Diels–Alder systems, 1, 3‐dipolar additions, or photodimerizations are successfully employed for the formation of precision polymeric networks with applications in a wide array of fields, entailing enticing prospects for future developments.